(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The first chapter included the introduction and the importance of the research to find new strategies to find out their effectiveness in the cognitive achievement of the subject of physical education and the methods of teaching sports sciences. The third chapter of physical education and sports sciences to determine the effects. The second chapter contained the methodology of the study and its field procedures, allowing the researcher to experiment with the method of comparative experimental samples. students, and the research sample was chosen by the intentional method, and they are (40) students in Division (C-D), so that Division (C) represents the control group, and Division (D) the experimental group, so that each group represents (20) students, so that the research sample constitutes (50%) ) from the research community, and for the purpose of the exploratory experiment, (10) students were chosen randomly from the research sample. As for the preparation sample, it included the entire research community, who are third-stage students. It amounted to (13) educational units, the time of the educational unit was (90) minutes. The third chapter included presenting, analyzing and discussing the results, and included a detailed presentation of the results of all tests. The fourth chapter included the most important conclusions, namely, that the Scamper strategy has a positive impact on the development of cognitive achievement of the subject of teaching methods for students of the third stage in the College of Physical Education and Sports Sciences - University of Wasit, and that the Scamper strategy contributed to increasing students’ self-confidence by providing them with the opportunity to generate ideas and apply them. He recommends The researcher emphasized the use of the Scamper strategy by teachers in developing the cognitive achievement of third-stage students because of its role in raising their scientific level in the subject of teaching methods. And positively involving students in the lesson and urging them to use their maximum potential and abilities in learning and developing their innovative thinking, as well as the need to use the Scamper strategy because it has effective countries in raising the scientific level of studentsKeywords: Scamper strategy, cognitive achievement, methods of teaching physical education and sports sciences.